Extraction Parameters Optimization of Sugarcane Wax from Filter Cake Using Taguchi Method - Lekhavat, Supaporn; Ookhawilai, Manunya; Siridamrong, Pornpen (Science Essence Journal, 2021)
Sugarcane is one of the most important economic crops in Thailand that the country was ranked as the world’s second largest exporter. Over the past decade, utilization of by-products such as bagasse, molasses and filter cake had been studied, in order to add value to the product, especially filter cake which contains natural wax. In this research, the sugarcane wax was extracted using the simple methods to provide the high yield and quality of the wax for further using in dental applications. The extraction conditions of sugarcane wax were designed based on Taguchi. Taguchi method with three factors and three levels of solid to liquid ratios (1/15, 1/20 and 1/25 g of filter cake/ml of solvent), extraction time (2, 4 and 6 hr) and extraction temperature (50, 60 and 70 ๐C) were used to obtain high extraction yield and high sugarcane wax quality. Grey relational analysis (GRA) was employed to convert multi-response problem into single response optimization. The results showed that extraction temperature exhibited the highest contribution for the obtained yield. A high solid to liquid ratio and a low temperature of extraction resulted in low quality of sugarcane wax in terms of melting and thermal degradation temperature. The highest extraction efficiency could be achieved at optimum parameter condition using 1g/15ml of solid to liquid ratio, 70๐C of extraction temperature and 6 hr of extraction time. Such findings from this research indicated that optimization by GRA was an effective tool to provide the highest extraction yield and properties.